Determinants of Zakat Compliance Behavior among Muslims Living Under Non-Islamic Governments - Adamu Ummulkhayr; Musa Yusuf Owoyemi; Rafidah Binti Mohammed Cusairi (International Journal of Zakat, 2017)
Zakat is one of the five pillars of Islam hence it is attracting a lot of scholarly attention. However, most of the existing literature on Zakat are concentrated in Islamic countries like Indonesia, Malaysia, Pakistan, Jordan, Saudi Arabia and others. There are also some researches in some advanced non-Islamic countries such as the USA and UK. In these countries, though the government does not operate Islamic laws, there are organized NGOs that take care of Islamic affairs including Zakat. However, there are many parts of the world where Muslims live under non-Islamic government and are not assisted by NGOs. In those areas, Muslims live and perform their religious obligations without any form of institutional support. There are limited number of research relating to Zakat in those areas. This study seeks to fill this gap by investigating the determinants of Zakat compliance in Kogi State of Nigeria. The study was conducted through qualitative interviews. Findings show that, the absence of governmental or institutional support results in ignorance, lack of organization and attitudinal problems. Recommendations were offered to assist Muslims in such areas. Keywords: Zakat compliance, Muslims in non-Islamic areas, Institutional support for Zakat